Strategi Pemasaran Pedagang Batagor: Studi Kasus Tentang Inovasi Dan Branding - Fini Welsa Agustin fini; Intan Maharani Putri; Wanda Nurjanah (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
This article is intended to recognize marketing strategies of batagor traders, with a focus on improving taste quality and branding. This research applies the case study method in a qualitative approach, and data was obtained through an interview process Batagor traders. The research results found that batagor traders were initially inspired to start a batagor business after experiencing a decline in turnover in their To business. They struggled hard to develop a batagor recipe that suited their tastes and the positive response from their neighbors encouraged them to start a wider batagor business. They maintain the quality of their merchandise with consistency in using recipes, making their own basic ingredients. and choose reliable raw material providers. The conclusion is that the success of Batagor traders is based on determination, perseverance, innovation and the ability to overcome various challenges in business. They maintain the quality of their merchandise with consistency in recipes and raw material management. Additionally, they try to maintain harmony between career and family life by scheduling quality time with their families and supporting each other. All of these elements play a role in achieving success for Batagor traders in running their business.